2021
DOI: 10.7717/peerj.11419
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antiaging properties of chlorogenic acid on UV-induced fibroblast cell

Abstract: Background Skin aging is the most common dermatological problem caused by intrinsic and extrinsic factor, such as exposure to (ultraviolet) UV rays. Chlorogenic acid (CA) is a phenolic compound which is known for its antioxidant properties against oxidative stress. Objective This study investigates the antiaging and anti-inflammatory properties of CA on UV-induced skin fibroblast cells. Methods Anti-inflammatory properties of CA were assessed by measuring inflammatory-related proteins IL-1β and TNF-α, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Among these, oddioside A ( 1 ) and compounds 5 , 6 , 7 , 8 , 10 , 13 , 14 and 15 showed strong MMP-1 inhibitory activity. Several compounds isolated in the present study have already been reported for various effects such as anti-inflammatory ( 9 , 10 , 13 , 14 , 15 , 16 ), antioxidant ( 3 , 4 , 5 , 8 , 9 , 13 , 14 , 15 , 19 ), and anti-aging ( 3 , 9 , 13 ) in various cell lines [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Thus, further experiments were focused on the new compound 1 to investigate its potential as a bioactive compound.…”
Section: Discussionmentioning
confidence: 66%
“…Among these, oddioside A ( 1 ) and compounds 5 , 6 , 7 , 8 , 10 , 13 , 14 and 15 showed strong MMP-1 inhibitory activity. Several compounds isolated in the present study have already been reported for various effects such as anti-inflammatory ( 9 , 10 , 13 , 14 , 15 , 16 ), antioxidant ( 3 , 4 , 5 , 8 , 9 , 13 , 14 , 15 , 19 ), and anti-aging ( 3 , 9 , 13 ) in various cell lines [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Thus, further experiments were focused on the new compound 1 to investigate its potential as a bioactive compound.…”
Section: Discussionmentioning
confidence: 66%
“…5,6 Excess ROS can directly lead to oxidative stress and pro-inflammatory responses in the skin, which cause further imbalance in the inflammatory response. [7][8][9] Specifically, under repeated and prolonged UV irradiation, the skin tissue produces a large amount of ROS that greatly exceeds the removal capability of endogenous defense systems. The excessive ROS directly cause oxidative stress damage to skin collagen (which contains numerous aliphatic and heterocyclic amino acids, and the side chains of the aliphatic amino acids and the heterocycles of the heterocyclic amino acids are just the sites attacked by ROS) 7,10 and activate IκB kinase (IKK).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al reported that CGA may suppress melanogenesis in B16 melanoma cells by inhibition of tyrosinase activity, implying the role of CGA on skin pigmentation [17]. Cha and Her et al showed that CGA could prevent against the skin aging induced by UVB radiation [18][19][20]. These reports were related to the protective effect of CGA against UVB-induced photoaging in keratinocytes, fibroblasts derived from newborn foreskin or hairless mice, as extrinsic skin aging is mainly associated with the solar ultraviolet (UV) radiation exposure [21].…”
Section: Introductionmentioning
confidence: 99%